Elektromiostimuljacija v kompleksnoj terapii narušenija venoznogo krovoobrašcenija nižnich konecnostej, voznikajušcego u vysokokvalificirovannych sportsmenov vsledstvie dlitel'nogo aviapereleta - Safonov, L. V.; Kozlovskij, A. P.; Šurygin, S. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The article is devoted to the improvement of the existing program of therapy of venous blood circulation disorders of the lower extremities in elite athletes, which is a consequence of the effect on the venous hemodynamics of the lower extremities of a complex of unfavorable factors associated with a long flight. A study was made of electromyostimulation of the lower extremities of highly qualified athletes in quality during a long flight. Based on the results of the studies, a program for the effective correction of hemodynamic and hypercoagulable disorders developing in highly qualified athletes dueto the adverse effect of long flight factors on the venous hemodynamics of the lower extremities is presented.